PEMANFAATAN TUMBUHAN OBAT DIABETES MELLITUS DI MASYARAKAT ETNIS SIMALUNGUN KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Helen Anjelina Simanjuntak (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2018)
Diabetes Mellitus is a health issue that attracts a lot of attention because of the prevalence rate that increases every year, especially in developing countries like in Indonesia. Diabetes Mellitus (DM) is a condition of decreasing the function of the pancreas to produce insulin or insulin receptors are not sensitive so that a metabolic disorder occurs where glucose is not converted into glycogen so that glucose can not enter the cells, resulting in increased blood glucose. Simalungun ethnic is one of the ethnic group in Simalungun Regency of North Sumatera Province where the society of Simalungun ethnic still utilize herbs as an alternative treatment like diabetes mellitus, so it is necessary to do research about the Utilization of Diabetes Mellitus Medicinal Plants In Simalungun Ethnic Society of Simalungun Regency of North Sumatera Province. This research was conducted using exploratory survey by the independent variable informant. Data collection was done by in-depth interview technique to informant. The results obtained 26 species of plants, consisting of, 20 families and 15 orders that have potential as an antidiabetic drug. Plant parts used are roots, leaves, fruit, stems, bark, seeds and tubers. And the most widely used is the leaves as much as 40.74%.